Evolutionarily significant units of the critically endangered leaf frog Pithecopus ayeaye (Anura, Phyllomedusidae) are not effectively preserved by the Brazilian protected areas network - Magalhães, Rafael Félix; Lemes, Priscila; Camargo, Arley; Oliveira, Ubirajara; Brandão, Reuber Albuquerque; Thomassen, Hans; Garcia, Paulo Christiano de Anchietta; Leite, Felipe Sá Fortes; Santos, Fabrício Rodrigues (Ecology and evolution, 2017)
Protected areas (PAs) are essential for biodiversity conservation, but their coverage is considered inefficient for the preservation of all species. Many species are subdivided into evolutionarily significant units (ESUs) and the effectiveness of PAs in protecting them needs to be investigated. We evaluated the usefulness of the Brazilian PAs network in protecting ESUs of the critically endangered Pithecopus ayeaye through ongoing climate change. This species occurs in a threatened mountaintop ecosystem known as campos rupestres. We used multilocus DNA sequences to delimit geographic clusters, which were further validated as ESUs with a coalescent approach. Ecological niche modeling was used to estimate spatial changes in ESUs’ potential distributions, and a gap analysis was carried out to evaluate the effectiveness of the Brazilian PAs network to protect P. ayeaye in the face of climate changes. We tested the niche overlap between ESUs to gain insights for potential management alternatives for the species. Pithecopus ayeaye contains at least three ESUs isolated in distinct mountain regions, and one of them is not protected by any PA. There are no climatic niche differences between the units, and only 4% of the suitable potential area of the species is protected in present and future projections. The current PAs are not effective in preserving the intraspecific diversity of P. ayeaye in its present and future range distributions. The genetic structure of P. ayeaye could represent a typical pattern in campos rupestres endemics, which should be considered for evaluating its conservation status. The effectiveness of protected areas (PAs) in preserving evolutionarily significant units (ESUs) needs to be investigated. We evaluated the usefulness of the Brazilian PAs network in protecting ESUs of the critically endangered Pithecopus ayeaye throughout ongoing climate change, delimiting its ESUs through a coalescent approach and evaluating the effectiveness of the actual coverage of PAs in the actual preservation of its intraspecific lineages. We found an ineffectiveness of these PAs in preserving the intraspecific diversity of P. ayeaye, in both its present and future suitable climatic niches, including one ESU which was unprotected in both of them, and pointing to the need to take the evolutionary potential of the species into account when designing PAs.